2014
DOI: 10.1590/0004-282x20140001
|View full text |Cite
|
Sign up to set email alerts
|

Developmental dyscalculia in children and adolescents with idiopathic epilepsies in a Brazilian sample

Abstract: Epilepsy is one of the most prevalent chronic disorders of childhood which can threaten child development and mental health. Among cognitive disorders, dyscalculia is one of the most important. In this study, 39 children and adolescents with idiopathic epilepsy underwent clinical and neuropsychological assessment to determine the intellectual level, math skills, reading and writing performance and neuropsychological profile. It was observed that the mathematical ability was below schooling expectations in a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
3
0
2
Order By: Relevance
“…O quarto artigo, com título traduzido para "Discalculia do Desenvolvimento em crianças e adolescentes com epilepsia idiopática em uma amostra brasileira" 26 , trata do estudo da avaliação clínica e neuropsicológica de crianças e adolescentes com epilepsia idiopática para determinar o nível intelectual, habilidades matemáticas, desempenho de leitura e escrita. Os instrumentos avaliativos utilizados foram: WISC-III, Teste de Atenção Seletiva e Sustentada, TDE, Prova Aritmética e Protocolo de Quadro 2 -Instrumentos utilizados e resultados das pesquisas dos artigos selecionados sobre avaliação da discalculia no período de 2010 a 2020.…”
Section: Resultsunclassified
“…O quarto artigo, com título traduzido para "Discalculia do Desenvolvimento em crianças e adolescentes com epilepsia idiopática em uma amostra brasileira" 26 , trata do estudo da avaliação clínica e neuropsicológica de crianças e adolescentes com epilepsia idiopática para determinar o nível intelectual, habilidades matemáticas, desempenho de leitura e escrita. Os instrumentos avaliativos utilizados foram: WISC-III, Teste de Atenção Seletiva e Sustentada, TDE, Prova Aritmética e Protocolo de Quadro 2 -Instrumentos utilizados e resultados das pesquisas dos artigos selecionados sobre avaliação da discalculia no período de 2010 a 2020.…”
Section: Resultsunclassified
“…There was a positive correlation between intelligence quotient and reading level in children and adolescents with idiopathic epilepsies [51].…”
Section: Demographic Psychosocial Factorsmentioning
confidence: 89%
“…Several studies have found in BECTS no significant differences regarding the onset age of epilepsy and the presence of any postmorbid neuropsychiatric problems [9,24,27,28,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51].…”
Section: Onset Agementioning
confidence: 99%
See 1 more Smart Citation
“…Pesquisas indicam que, em geral, os limites e dificuldades para aquisição de conhecimento matemático relacionam-se diretamente a restrições no processo de aprendizagem das habilidades aritméticas, compreensão de conceitos numéricos simples e entendimento de procedimentos matemáticos (Thomé et al, 2014). Nesse sentido, a tarefa do pesquisador inclui o detalhamento da análise investigativa sobre déficits cognitivos de modo a evitar erros na intervenção e no diagnóstico (Haase et al, 2012).…”
Section: Neuropsicologia: Aspectos Conceituais E Relevância Para a Avaliaçãounclassified